COMMUNITY KNOWLEDGE OF ARJOSARI VILLAGE, KALIPARE DISTRICT, MALANG DISTRICT, EAST JAVA ABOUT SAVING OF RAINWATER - Rahmah Dara Lufira; Lilik Zuhriyah; Satwika Desantina Muktiningsih; Aldila Putri Rahayu; Ken Diah Mangar Nastiti (International Journal of Educational Management and Innovation, 2021)
Arjosari Village, Kalipare Subdistrict, Malang Regency, experiences drought every year; this makes the villagers buy water when the dry season comes. This research aims to find out how much knowledge of the people of Arjosari Village, Kalipare District, Malang Regency in saving rainwater used as an alternative to fulfil water needs in the dry season. The research method used was a descriptive survey method with a sample of 82 people. Survey studies are "a observe that takes samples from a single population and uses questionnaires as a primary records series tool". The results showed that the community's knowledge of the concept of saving rainwater was "high".Meanwhile, for the public's knowledge of methods of saving rainwater, there were 26 people in the "Low" category, 40 people in the "Medium" category, and 16 in the "High" category. Methods that can save rainwater are the construction of rainwater infiltration wells, bio pure infiltration holes, rainwater harvesting, and appropriate vegetation selection. This education can give the benefits that increase the public knowledge and awareness to conduct groundwater conservation to anticipate the lack of clean water in this area.